ANALISIS KEKUATAN IMPACT BAHAN MIXER BLADE AKIBAT PENGARUH HEAT TREATMENT - Ihya Sulaiman, Muhamad Yusril; Hamdani, R. Aam; Wardaya; Komaro, Mumu (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
Mixer blade is one of the tools used in the cement industry as a tool to mix the composition of raw cement into ready-to-use cement. However, in its use, damage is often caused when the mixing process takes place, there is material that is too hard and makes the blade break. Based on these problems, the author made a study entitled "Analysis of the Difference in Impact Strength of Mixer Blade Materials Due to the Heat Treatment Process". This study aims to determine the difference in impact strength received by the mixer blade material after the heat treatment process. The Heat Treatment processes carried out are Quenching, Carburizing, and Tempering. The method used in this research is the experimental method. The process of making specimens is carried out in the UPI Mechanical Engineering Education Design Production lab. The Heat Treatment process is carried out at the POLMAN Manufacturing Process Lab. And for the process of testing material properties, it is carried out at the Metallurgical Lab of UPI Mechanical Engineering Education. The material of this mixer blade is low carbon steel so that the carburizing process is chosen. The carburizing process was carried out with a carburizing medium (carburizer) a mixture of 60% coconut shell charcoal and 40% NaCo3 (weight ratio) at a temperature of 850°C and held for 90 minutes. Cooling is done by storing the specimen in the furnace so that cooling is slow. Followed by a tempering process at a temperature of 500°C and held for 60 minutes and carried out a quenching process with free air. There is a difference in the impact strength of the object from 1.84 J/mm2 to 0.81 J/mm2 and a difference in surface hardness from 85.67 HRB to 92.83 HRB.